Curcumin Successfully Inhibited the Computationally Identified CYP2A6 Enzyme-Mediated Bioactivation of Aflatoxin B1 in Arbor Acres broiler - Muhammad, Ishfaq; Sun, Xiaoqi; Wang, He; Li, Wei; Wang, Xinghe; Cheng, Ping; Li, Sihong; Zhang, Xiuying; Hamid, Sattar (Frontiers in Pharmacology, 2017)
Cytochrome P450 enzymes are often responsible for the toxic and carcinogenic effects of toxicants, such as aflatoxin B1 (AFB1). The human hepatic CYP2A6 enzyme mediates the oxidative metabolism of several procarcinogens. In this study, we characterized a partial sequence of CYP2A6 gene from Arbor Acres (AA) broiler and studied its role in AFB1 bioactivation. Moreover, the effect of curcumin on CYP2A6 is illustrated. Six groups of AA broiler were treated for 28 day including the control group (fed only basal diet), curcumin alone-treated group (450 mg/kg feed), the group fed AFB1-contaminated feed (5 mg/kg feed) plus the low (150 mg), medium (300 mg) or high (450 mg) of curcumin, and the group fed AFB1-contaminated diet alone (5 mg/kg feed). After the end of treatment period, liver samples were collected for different analyses. The results revealed that the histopathological examination showed clear signs of liver toxicity in AA broliers in AFB1-fed group, but curcumin-supplementation in feed prevented partially AFB1-induced liver toxicity. Liver and body weights were recorded to study the AFB1 harmful effects. We noted an obvious increase in liver weight and decrease in body weight in AFB1-fed group. But, the administration of curcumin partially ameliorated the increase in liver weight and decrease in body weight in a dose-dependent manner. The results (RT-PCR and Elisa) revealed that mRNA and protein expression level enhanced in AFB1-fed group. Consistently, CYP2A6 enzyme activity also increased in AFB1-fed group, suggesting that AA broiler CYP2A6 actively involved in bioactivation of AFB1. However, curcumin treatment inhibited CYP2A6 at mRNA and protein levels in AFB1 treated AA broiler in a dose-dependent manner. Maximum inhibition of liver CYP2A6 enzyme activity in AA broiler has been achieved at a dose of 450 mg/kg curcumin. This is the first study identifying and confirming the role of CYP2A6 enzyme in AFB1 bioactivation in AA broiler liver (in-vivo), and the hepatoprotective role of curcumin via inhibiting CYP2A6 expression and enzyme activity. The study contributed to identify an important CYP enzyme involved in AFB1 bioactivation in broilers and thus could pave the way for the prevention of the harmful effects of AFB1 in broilers.